2018
DOI: 10.15244/pjoes/78042
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Removal by Photocatalytic Process from Aqueous Solution

Abstract: The entry of gentamicin antibiotics into the aquatic environment has raised many concerns. Today, modern nanotechnology-based approaches have been employed to overcome such problems. The present study was conducted to investigate the efficiency of the UV/ZnO photocatalytic process in removing antibiotic gentamicin from aqueous solution. So we investigated the effects of parameters, including initial gentamicin concentrations (20, 60, and 100 mg/L), zinc oxide concentrations (0, 200, 350, and 500 mg/L), contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The reason for the high removal efficiency at the initial moments was the number of active adsorbent positions available for receiving UV photons. However, over time, these sites were saturated, with the rate of degradation decaying significantly and eventually reaching equilibrium conditions [42,43]. In the study of Zhang et al in 2013 on removal of methylene blue from wastewater using the photocatalysts TiO 2 and ZnO, the highest removal efficiency was observed at 90 min, which is similar to the present study [44].…”
Section: Effect Of Reaction Time On the Responsesupporting
confidence: 87%
“…The reason for the high removal efficiency at the initial moments was the number of active adsorbent positions available for receiving UV photons. However, over time, these sites were saturated, with the rate of degradation decaying significantly and eventually reaching equilibrium conditions [42,43]. In the study of Zhang et al in 2013 on removal of methylene blue from wastewater using the photocatalysts TiO 2 and ZnO, the highest removal efficiency was observed at 90 min, which is similar to the present study [44].…”
Section: Effect Of Reaction Time On the Responsesupporting
confidence: 87%
“…Other studies have already reported these photocatalytic effects of antibiotics, such as the degradation of norfloxacin hydrochloride [ 36 ], gentamicin [ 37 ], and amikacin [ 38 ], so it becomes increasingly important, studies of synthesis and application of nanostructured materials for environmental recovery, since the inefficiency of effluent treatment methods or even the absence of these in municipalities, associated with the exacerbated consumption of antibiotics, contribute to the ubiquity of these drugs in various environments, especially aquatic, increasing the proliferation of multidrug-resistant bacteria and toxicity, which makes it essential, the development of new efficient tools to degrade these compounds [ 39 ].…”
Section: Resultsmentioning
confidence: 99%